Novel non-heteroarylpyrimidine (HAP) capsid assembly modifiers have a different mode of action from HAPs in vitro - Corcuera, Angelica; Stolle, Katharina; Hillmer, Stefan; Seitz, Stefan; Lee, Ji Young; Bartenschlager, Ralf; Birkmann, Alexander; Urban, Andreas (Antiviral research, 2018)
One of the most promising viral targets in current hepatitis B virus (HBV) drug development is the core protein due to its multiple roles in the viral life cycle. Here we investigated the differences in the mode of action and antiviral activity of representatives of six different capsid assembly modifier (CAM) scaffolds: three from the well-characterized scaffolds heteroarylpyrimidine (HAP), sulfamoylbenzamide (SBA), and phenylpropenamide (PPA), and three from novel scaffolds glyoxamide-pyrrolamide (GPA), pyrazolyl-thiazole (PT), and dibenzo-thiazepin-2-one (DBT). The target activity and antiviral efficacy of the different CAMs were tested in biochemical and cellular assays. Analytical size exclusion chromatography and transmission electron microscopy showed that only the HAP compound induced formation of aberrant non-capsid structures (class II mode of action), while the remaining CAMs did not affect capsid gross morphology (class I mode of action). Intracellular lysates from the HepAD38cell line, inducibly replicating HBV, showed no reduction in the quantities of intracellular core protein or capsid after treatment with SBA, PPA, GPA, PT, or DBT compounds; however HAP-treatment led to a profound decrease in both. Additionally, immunofluorescence staining of compound-treated HepAD38cells showed that all non-HAP CAMs led to a shift in the equilibrium of HBV core antigen (HBcAg) towards complete cytoplasmic staining, while the HAP induced accumulation of HBcAg aggregates in the nucleus. Our study demonstrates that the novel scaffolds GPA, PT, and DBT exhibit class I modes of action, alike SBA and PPA, whereas HAP remains the only scaffold belonging to class II inhibitors.